Feasibility Analysis of Clean Water System Investment of Tirta Tuah Benua Drinking Water Company, East Kutai, Kaliorang District - Rahmawati, Rini; Oetomo, Wateno; Marleno, Risma (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
Water is a very vital natural resource and is needed to determine the sustainability of life of all living things on this earth. The problem faced is that the clean water system to residential areas is not smooth, to overcome this, a good clean water distribution network and good clean water system management are needed and are able to serve the clean water needs of residents in the area. In order to realize this, a fairly large investment is needed. One of them is by implementing company investment in the form of increasing the capacity of the raw water supply system. Based on the background mentioned, the title of this study is Feasibility Analysis of Clean Water System Investment at Perumda Air Minum Tirta Tuah Benua Kutai Timur, Kaliorang District. The solution method in this calculation for Feasibility Investment Analysis uses the Net Present Value (NPV) method, the Internal Rate of Return (IRR) method. From the results of the analysis, it was obtained that the NPV value was IDR 4,627,419,730 (NPV> 0). So the investment in developing production capacity and clean water networks at Perumda Air Minum Tirta Tuah Benua, Kaliorang District, is feasible to continue. A positive NPV value or greater than (>0) indicates that the income is greater than the invested value. The IRR value obtained is 15.50% > 10% (the minimum expected interest rate), so the investment in developing the production capacity and clean water network of Perumda Air Minum Tirta Tuah Benua, Kaliorang District is feasible to be implemented.